Analytical and Sales Data Comparison of Reference Product of Insulin Aspart and its Biosimilar in Turkey - SEZER, ALİ DEMİR (MARMARA UNIV, FAC PHARMACY, 2017)
In recent years, biosimilar products have become one of the most popular areas of pharmaceutical industry and pharmaceutical biotechnology. As their patents have expired or are about to expire, biotechnology products, whose manufacture involves more complex processes, are becoming a focus of interest. Compared to generic products, complex processes are not limited to manufacture. Preclinical and clinical development as well as market access process for biosimilar biological products is also challenging and costly. Despite these challenges, many companies continue to develop biosimilar products. Despite the fact that there are long-term robust data related to generics, the debate of many topics for biosimilar has just begun. These topics include the economic contribution of biosimilar, public cost effects, patient access, clinical trials and trials comparative with the reference product. Within the scope of this study, global and Turkey sales data of biological products containing insulin which was initially approved in 1982 and was produced by recombinant DNA technology were reviewed. The study also covered the analytical comparison of the reference insulin aspart with insulin aspart biosimilar products and discussed the possible topics that could be used in development and registration processes.
Keywords: Biotechnological medicine; Biosimilar; insulin; insulin aspart; peptide mapping; DRUGS